2015
DOI: 10.1186/s12868-015-0212-0
|View full text |Cite
|
Sign up to set email alerts
|

T cell deficiency in spinal cord injury: altered locomotor recovery and whole-genome transcriptional analysis

Abstract: BackgroundT cells undergo autoimmunization following spinal cord injury (SCI) and play both protective and destructive roles during the recovery process. T cell-deficient athymic nude (AN) rats exhibit improved functional recovery when compared to immunocompetent Sprague–Dawley (SD) rats following spinal cord transection.MethodsIn the present study, we evaluated locomotor recovery in SD and AN rats following moderate spinal cord contusion. To explain variable locomotor outcome, we assessed whole-genome express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Though HuSCs were transplanted at 1 month after SCI they could have still mediated protective effects on the host as ongoing changes in the evolution of injury have been reported at this time, including processes of Wallerian degeneration, demyelination and inflammation (Hagg and Oudega, ; Iizuka, Yamamoto, Iwasaki, Yamamoto, & Konno, ; Schwab, Zhang, Kopp, Brommer, & Popovich, ). In addition, the altered immunological status of the nude rat may have produced a delay in the timing of these pathological processes with the absence of T‐cell‐mediated inflammation as previously reported (Satzer et al, ). Observed differences in white matter volume could have been produced not only from a reduction in demyelination but also through an enhancement of endogenous remyelination.…”
Section: Discussionmentioning
confidence: 57%
“…Though HuSCs were transplanted at 1 month after SCI they could have still mediated protective effects on the host as ongoing changes in the evolution of injury have been reported at this time, including processes of Wallerian degeneration, demyelination and inflammation (Hagg and Oudega, ; Iizuka, Yamamoto, Iwasaki, Yamamoto, & Konno, ; Schwab, Zhang, Kopp, Brommer, & Popovich, ). In addition, the altered immunological status of the nude rat may have produced a delay in the timing of these pathological processes with the absence of T‐cell‐mediated inflammation as previously reported (Satzer et al, ). Observed differences in white matter volume could have been produced not only from a reduction in demyelination but also through an enhancement of endogenous remyelination.…”
Section: Discussionmentioning
confidence: 57%
“…33 In athymic nude rats, which do not have T lymphocytes, NK cell markers were elevated intraspinally at 8 weeks post-injury, whereas motor recovery was only improved at 1 week post-injury, compared to Sprague-Dawley rats. 48 …”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immune cells, such as T cells are thought to inhibit regeneration in mammals, as their depletion improves injury outcomes [41,42]. It has recently been shown that depletion of regulatory T cells in a spinal injury site in adult zebrafish strongly inhibits regeneration of axons, progenitor cell proliferation, addition of new neurons and functional recovery [43].…”
Section: Adaptive Immune Cellsmentioning
confidence: 99%